Cathodic hydrodimerization of nitroolefins - Weßling, Michael; Schäfer, Hans J. (Beilstein Journal of Organic Chemistry, 2015)
Nitroalkenes are easily accessible in high variety by condensation of aldehydes with aliphatic nitroalkanes. They belong to the group of activated alkenes that can be hydrodimerized by cathodic reduction. There are many olefins with different electron withdrawing groups used for cathodic hydrodimerization, but not much is known about the behaviour of the nitro group. Synthetic applications of this group could profit from the easy access to nitroolefins in large variety, the C–C bond formation with the introduction of two nitro groups in a 1,4-distance and the conversions of the nitro group by reduction to oximes and amines, the conversion into aldehydes and ketones via the Nef reaction and base catalyzed condensations at the acidic CH bond. Eight 1-aryl-2-nitro-1-propenes have been electrolyzed in an undivided electrolysis cell to afford 2,5-dinitro-3,4-diaryl hexanes in high yield. The 4-methoxy-, 4-trifluoromethyl-, 2-chloro- and 2,6-difluorophenyl group and furthermore the 2-furyl and 2-pyrrolyl group have been applied. The reaction is chemoselective as only the double bond but not the nitro group undergoes reaction, is regioselective as a ß,ß-coupling with regard to the nitro group and forms preferentially two out of six possible diastereomers as major products.
Keywords: cathodic hydrodimerization; C–C bond formation; 1,4-dinitrocompounds; electrosynthesis; nitroalkene